A case study eveluating the University's instructors' acceptance of E- Learning syatem - 612930 Hii Puong Koh, 1994-, author; Goh, Chin Fei, 1981- supervisor 569074; Fakulti Pengurusan 538641 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Project Paper (Sarjana Muda Pengurusan (Teknologi)) - Universiti Teknologi Malaysia, 2017